Primary hyperoxaluria: Comprehensive mutation screening of the disease causing genes and spectrum of disease‐associated pathogenic variants. Issue 1 (9th October 2022) - Abid, Aiysha; Raza, Ali; Khan, Abdul Rafay; Firasat, Sadaf; Shahid, Saba; Hashmi, Seema; Zafar, Mirza Naqi; Sultan, Sajid; Khaliq, Shagufta; Rizvi, Syed Adib‐ul‐Hasan
Abstract: The primary hyperoxalurias are rare disorders of glyoxylate metabolism. Accurate diagnosis is essential for therapeutic and management strategies. We conducted a molecular study on patients suffering from recurrent calcium‐oxalate stones and nephrocalcinosis and screened primary hyperoxaluria causing genes in a large cohort of early‐onset cases. Disease‐associated pathogenic‐variants were defined as missense, nonsense, frameshift‐indels, and splice‐site variants with a reported minor allele frequency <1% in controls. We found pathogenic‐variants in 34% of the cases. Variants in the AGXT gene causing PH‐I were identified in 81% of the mutation positive cases. PH‐II‐associated variants in the GRHPR gene are found in 15% of the pediatric PH‐positive population. Only 3% of the PH‐positive cases have pathogenic‐variants in the HOGA1 gene, responsible to cause PH‐III. A population‐specific AGXT gene variant c.1049G>A; p.Gly350Asp accounts for 22% of the PH‐I‐positive patients. Pathogenicity of the identified variants was evaluated by in‐silico tools and ACMG guidelines. We have devised a rapid and low‐cost approach for the screening of PH by using targeted‐NGS highlighting the importance of an accurate and cost‐effective screening platform. This is the largest study in Pakistani pediatric patients from South‐Asian region that also expands the mutation spectrum of the three known genes. Abstract : We screened a cohort of Pakistani pediatric patients suffering from recurrent calcium‐oxalate stones and nephrocalcinosis for primary hyperoxaluria‐causing genes. Pathogenic‐variants are identified in 34% of the cases. We devise a robust approach for the screening of PH by using targeted NGS, highlighting the significance of an accurate and cost‐effective screening platform. It is the most extensive study conducted on a population from the South‐Asian region that expands the mutation spectrum of the three known genes.